Anaphylaxis after zoster vaccine: Implicating alpha-gal allergy as a possible mechanism - Stone, Cosby A.; Hemler, Jonathan A.; Commins, Scott P.; Schuyler, Alexander J.; Phillips, Elizabeth J.; Peebles, R. Stokes; Fahrenholz, John M. (Journal of allergy and clinical immunology, 2017)
Gelatin and other nonprimate mammal-derived products are common excipient ingredients in several vaccines,2,3 and it has been postulated that patients with alpha-gal allergy might react to these vaccines.4 A patient in our clinic with a documented history of red meat allergy since November 2008 required emergency department treatment and epinephrine administration on receipt of live attenuated herpes zoster vaccine containing the Oka varicella zoster virus strain in September 2014. There was also low positive binding (values, 0.27-0.45 IU/mL) for MMR and zoster vaccine in sera from subjects A and B that could be removed by the presence of bovine thyroglobulin, although sera from subject C did not demonstrate binding to any of the candidate vaccines. To ascertain the presence of vaccine epitopes that would bind/remove alpha-gal-specific IgE in excess of that expected for gelatin alone, we incubated serum samples from the index patient and the 3 subjects with positive alpha-gal results overnight separately with 100 μg from each of the 5 vaccines, bovine gelatin, and porcine gelatin and remeasured alpha-gal IgE titers. Reported sIgE levels were as follows: porcine gelatin, 0.58 kU/L; bovine gelatin, <0.10 kU/L; and alpha-gal, 3.70 kU/L Maryland References 1 S. Commins, S.M. Satinover, J. Hosen, L. Mozena, L. Borish, B.D. Lewis, Delayed anaphylaxis, angioedema, or urticaria after consumption of red meat in patients with IgE antibodies specific for galactose-alpha-1,3-galactose, J Allergy Clin Immunol, Vol. 123, 2009, 426-433 2 J. Kelso, M. Greenhawt, J. Li, R. Nicklas, D. Bernstein, J. Blessing-Moore, Adverse reactions to vaccines practice parameter...